2015
DOI: 10.1130/g36669.1
|View full text |Cite
|
Sign up to set email alerts
|

Is the present the key to the past? A global characterization of modern sedimentary basins

Abstract: The stratigraphic record is heavily biased because it is uniquely composed of sediments that were laid down in basins, whereas the majority of the present and historic land surface of the planet is composed of areas that are in net long-term erosion with no preservation potential. Global mapping and quantification of the distribution of currently active sedimentary basins suggest that only 16% of Earth's terrestrial land surface is within sedimentary basins; the remainder of the land is in upland areas that wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
49
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(52 citation statements)
references
References 18 publications
3
49
0
Order By: Relevance
“…Nyburg and Howell (2015) showed that 93 modern continental sedimentary basins cover only ~16% of the current continental area if one excludes 94 the passive margin setting, thus only deposits from a relatively small portion of the modern continental 95 area will ultimately be preserved in the sedimentary rock record. 96 Weissmann et al (2010) and comprise most but not all of the fluvial deposits in these basins.…”
Section: Introduction 70mentioning
confidence: 99%
“…Nyburg and Howell (2015) showed that 93 modern continental sedimentary basins cover only ~16% of the current continental area if one excludes 94 the passive margin setting, thus only deposits from a relatively small portion of the modern continental 95 area will ultimately be preserved in the sedimentary rock record. 96 Weissmann et al (2010) and comprise most but not all of the fluvial deposits in these basins.…”
Section: Introduction 70mentioning
confidence: 99%
“…Sedimentary basins are areas in which tectonic subsidence of the Earth's crust has occurred, creating accommodation within which sedimentary successions can be deposited and, importantly, be preserved (e.g. Allen & Allen, 1990;Weissmann et al, 2010;Nyberg & Howell, 2015). By studying the deposits of continental sedimentary basins, insights can be gained into past terrestrial environments, as well as changes in climate, tectonics and base level, throughout Earth's history (Bridge, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Because of this net uplift, this sedimentary record is ephemeral and unlikely to persist into deep geological time (i.e. more than 1-10 Myr) [20,22], and these deposits can be considered 'doomed sediments'. This decrease in the quantity of the stratigraphic record backward through time, as well as its accessibility at Earth's surface, are major causes of the pull of the recent, where the quality of fossil record declines with geological age [23,24].…”
Section: (A) Extent Of Sedimentary Basinsmentioning
confidence: 99%
“…16% today [20]). Other areas that are undergoing uplift and erosion supply sediment to the basins, in addition to carbonate sediments produced by organisms living primarily within marine environments.…”
Section: (A) Extent Of Sedimentary Basinsmentioning
confidence: 99%
See 1 more Smart Citation